Pendampingan Strategi Pemasaran Digital Marketing pada UMKM Desa Semanding, Kecamatan Jenangan - Muh Nur Luthfi Azis; Alim Citra Aria Bima; Gilang Romadhon (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Micro, Small and Medium Enterprises (MSMEs) are one of the important sectors in the Indonesian economy. In this digital era, MSMEs need to utilize digital marketing strategies to increase their competitiveness. This journal describes digital marketing strategy assistance activities carried out for MSMEs in Semanding Village, Jenangan District. This activity aims to increase the knowledge and skills of MSME players in using digital media to market their products. The methods used in this activity are socialization, training and individual mentoring. The results show that this activity increases the knowledge and skills of MSME players in using digital media to market their products. This is proven by the increasing number of MSMEs that have social media accounts and online shops. Apart from that, this activity also increases sales of MSME products. This shows that digital marketing strategies are effective in increasing the competitiveness of MSMEs in Semanding Village.